Perception, Vulnerability, and Adaptation to Climate Change Impacts: A Case Study of Coastal Livelihoods in Chilaw, Sri Lanka - Bulathsinhalage, Buddika Manori Bulathsinhala (Curtin University, 2021)
The study investigates the process of adaptation in view of livelihood vulnerability of coastal communities encompassing their perceptions of climate change impacts, both in quantitative and qualitative terms. Despite direct exposure, climate change is often an abstract and distant concept for coastal communities. Being the first in-depth empirical study conducted in Sri Lanka, it introduces the tools of “livelihood vulnerability index” and “perception index” to assist all levels of stakeholders to combat climate change effects.